Small-angle neutron scattering investigations of nanocrystalline alloy chips obtained by machining - Elwyn Rebello; Frazer Vaz; Avino Colaco; Wellon Rodrigues; Geethalakshmi K; Debasis Sen; S. Mazumder; A.O. Surendranathan (Cogent Engineering, 2014)
Ultrafine-grained (UFG) materials exhibit significantly enhanced mechanical properties. This has brought renewed attention on the use of large strain or severe plastic deformation as a means for achieving microstructural refinement in metals and alloys. Large plastic strains imposed in a machine chip result in significant microstructural refinement, including the creation of UFG and nanocrystalline materials. It looks to be an economical route for realizing nanocrystalline materials. In the present study, small-angle neutron scattering (SANS) was employed to investigate the modifications in the microstructure of the chips produced via machining. Double crystal-based medium resolution SANS instrument has been used for this purpose. Significant scattering intensity at small enough angles reveals the presence of mesoscopic density fluctuations produced because of the machining. Atomic force microscopy images also corroborate the existence of such small length scale density fluctuations.